SME contractors’ management practices to achieve sustainable business performance in the Eastern Cape province, South Africa - Athenkosi Sogaxa (Acta Structilia)
The construction industry in the Eastern Cape province of South Africa plays a crucial role in the region’s economy, yet small and medium enterprise (SME) construction companies face significant challenges in achieving long-term business sustainability. This article aims to provide practical guidelines for SMEs, by investigating the most critical construction management practices adopted by SME contractors. Utilising a quantitative approach, data were collected from 59 purposefully selected participants, including directors, construction managers, quantity surveyors, site agents, and technicians, all registered under the Construction Industry Development Board (CIDB) Grades 1-4 in General Building (GB). The management practices of SME contractors were analysed using the relative importance index (RII) and factor analysis to rank these practices according to their significance. Findings indicate that SME contractors prioritise health and safety strategies, effective resource utilisation, integrated project management systems, competent recruitment, strong leadership skills, and robust health and safety management as essential practices. The principal component analysis identified six key management factors to enhance competitiveness while contributing to the region’s sustainable development goals. These factors include shared knowledge among management, effective project scope planning, comprehensive health and safety management, ownership of construction business knowledge, scope control on projects, and clearly defined goals for management teams. This study is original in its focus on the specific management practices that can strengthen the sustainability of SME contractors within a developing region, providing a valuable framework for enhancing their operational effectiveness.